2006
DOI: 10.1111/j.1365-3024.2006.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Schistosoma mansoni by transplantation of APO Biomphalaria tenagophila

Abstract: Transplantation of the haematopoietic organ from Biomphalaria tenagophila (Taim strain, RS, Brazil), resistant to Schistosoma mansoni, to a highly susceptible strain (Cabo Frio, RJ, Brazil) of the same species, showed in the recipient snails resistance against the trematode, when a successful transplant occurred. The success of transplantation could be confirmed by a typical molecular marker of the Taim strain in haemocytes of the recipients (350 bp detected by PCR-RFLP). The recipient snails which did not pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Several studies have been carried out in order to gain a better understanding of resistance traits, including molecular approaches using nuclear DNA regions (Pires et al 1997, Spatz et al 1999, Barbosa 2001, Rosa et al 2005, Barbosa et al 2006), but little is known about the genes related with the resistance phenotype in this population (Santos et al 1979, de Freitas et al 1985, Rosa 2002.…”
mentioning
confidence: 99%
“…Several studies have been carried out in order to gain a better understanding of resistance traits, including molecular approaches using nuclear DNA regions (Pires et al 1997, Spatz et al 1999, Barbosa 2001, Rosa et al 2005, Barbosa et al 2006), but little is known about the genes related with the resistance phenotype in this population (Santos et al 1979, de Freitas et al 1985, Rosa 2002.…”
mentioning
confidence: 99%
“…Furthermore, experimental transplantation of several organs from B. glabrata specimens from a strain partially resistant to S. mansoni infection to individuals from a susceptible strain, demonstrated that the APO was unique in its ability of transfering resistance to the receptors (Sullivan & Spence 1994). More recently, Barbosa et al (2006) transformed susceptible strains of B. tenagophila into resistant ones by transplantation of the APO from an absolute resistant strain (Taim, RS, Brazil) of the same mollusk species. The transplanted recipients became completely resistant to S. mansoni infection.…”
mentioning
confidence: 99%
“…Recent studies have confirmed that successful transplantation of the amoebocyte-producing organ from the B. tenagophila Taim isolate to the susceptible B. tenagophila Cabo Frio isolate caused the susceptible organism to be partially refractive to S. mansoni infection (Barbosa et al 2006), indicating that immunological processes play an important role in resistance to infection. In addition, Pereira (2005) and Bezerra and Coelho (2006) showed that inoculation of the hemolymph from B. tenagophila Taim to a susceptible isolate of B. tenagophila promotes a state of resistance against S. mansoni miracidia infection.…”
Section: Discussionmentioning
confidence: 90%
“…Studies with the B. tenagophila Taim lineage have demonstrated its natural resistance to S. mansoni infection and experiments to alter its refractoriness have, until the present, failed (Bezerra et al 2003, Barbosa et al 2006.…”
mentioning
confidence: 99%